The Epidemiology and Control of “Olive Quick Decline Syndrome” in Salento (Apulia, Italy) - Marco Scortichini (Agronomy, 2022)
Xylella fastidiosa subsp. pauca sequence type 53 was found to be associated with olive trees showing extensive twig and branch dieback and plant death in the Gallipoli area of Salento and the common name of “olive quick decline syndrome” (OQDS) was given to the disease. Repeated interceptions in Europe and Italy of ornamental coffee plants originated from Central America, jointly in phylogenetic analyses of many strains of the pathogen, indicated this origin as the most probable source of its introduction in Salento. Drought events could have been conducive to the initial outbreaks of the disease. Subsequently, the pathogen largely spread over the territory according to a “stratified dispersal” model. The high susceptibility of the local cultivars Ogliarola salentina and Cellina di Nardò, a low soil content of zinc, copper, and manganese, improper pruning, and adverse climatic events could have further contributed to the spread of the pathogen. The polyphagous insect Philaenus spumarius L. is the main vector of the bacterium in the area. The adults were detected X. f. subsp. pauca-positive in early May, and their incidence was higher during spring and early autumn when they efficiently spread the bacterium among the olive trees. Many other host plant species can host the bacterium, and some of them can act as a “reservoir” for the disease spread. The aggressive fungus Neofusicoccum mediterraneum Crous, M.J. Wingf. And A.J.L. Philips, could also be involved in OQDS. A sustainable control strategy for reducing the incidence and severity of X. f. subsp. pauca in the olive groves of Salento that allows the trees to produce is presented and discussed. Resilient trees of Ogliarola salentina and Cellina di Nardò have been observed in the heavily infected areas of Salento.